PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP PEMAHAMAN DAN MOTIVASI SISWA SD KELAS 5B PADA MATA PELAJARAN MATEMATIKA DI SD MUHAMMADIYAH 1 BANGKALAN - Riezal Muhaimin; Ihwan Firmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aimed to assess the influence of the talking stick learning model on students' comprehension and motivation at SD Muhammadiyah 1 Bangkalan. The quantitative method employed was a Pre-Experimental Designs experiment using a One Group Pretest-Posttest Design. The study utilized tests for validity, reliability, normality, and the Paired Sample T-Test Hypothesis in data analysis. Results indicated a significant improvement in student comprehension and motivation, as confirmed by SPSS analysis validating its high impact. The Paired Sample T-Test showed a noteworthy increase in motivation (from 14.35 to 36.00) and comprehension (from 5.54 to 13.46).